Indigenous Whaling Tradition in Faroe Islands under International Law - Setyonugroho, Olivia Martha; Wisanjaya, I Gede Pasek Eka; Yasa, Made Maharta (Udayana Journal of Law and Culture, 2019)
The issue of whaling has been extensively debated in various international occasions since it causes a declines in many of the world’s whale population. Presently, Faroe Islands is one of the few regions in Denmark that still adamantly practiced whaling for traditional purposes, even though Denmark itself has prohibit it. This writing aims to analyze the whaling tradition in Faroe Islands from the International Law perspective. Further, to examine whether Denmark has an international obligation to end whaling activities in Faroe Islands. The method that is used in this writing is the normative legal research. The result of this analysis shows that the tradition in Faroe Islands is consistent with International Law, thus Denmark has no international obligation to end the tradition.